Determination of Hydrogen Fluoride in Uranium Hexafluoride by FTIR - E. Kazeman; M. Adineh; A. Khagezadeh; H. Shah mir Barzoki; V. Chegini (مجله علوم و فنون هسته‌ای, 2020)
High reactivity of uranium hexafluride compound is responsible for the impurity production of hydrogen fluoride in the enrichment industry process. The presence of this interference gas will disrupt uranium enrichment process. For this reason, measurement of hydrogen fluoride gas in uranium hexafluoride matrix as one of the important factors in the enrichment industry was carried out by FTIR spectrometry. Using of a new manifold system and a 10 m pathlength reflectance gas cell can lead to perform the analysis of hydrogen fluoride in the easier and more appropriate conditions than the ASTM method. The results obtained from the optimization of the present method are as flow: reduction of utilized UF6 (≈ 80%), elimination of liquid N2 for sample preparation, and simplification of sampling. Among the five standards and international regulations available, the ISO/IEC 17025 standard considerations is used, and verification parameters such as linearity, accuracy, precision, detection limit, quantization limit, and uncertainty of the results for the effect of the existing errors were studied.